Do Our Patients Really Need Telerehabilitation? Digital Physical Therapy for Boys with Duchenne Muscular Dystrophy in the COVID-19 Pandemic - Agnieszka Sobierajska-Rek; Łukasz Mański; Joanna Jabłońska-Brudło; Karolina Śledzińska (Medical Sciences Forum, 2022)
The COVID-19 pandemic forced the reorganization of the multidisciplinary healthcare system for Duchenne muscular dystrophy (DMD). Digital solutions seemed to be an optimal way for providing rehabilitation during this time. The aim of our study was to investigate whether it is possible to conduct respiratory physical therapy with the use of telerehabilitation methods in boys with Duchenne muscular dystrophy. Methods: The study was conducted during the online conference ‘DMD—Let’s be together’ for Polish families with DMD. During the physical therapy panel, we showed the video with the instructions of respiratory exercises: glossopharyngeal breathing, positive inspiratory pressure, and positive expiratory pressure. All participants (n = 152) were asked to fill in the online survey evaluating the quality of the instructions, its acceptance, and understanding. Results: The survey was filled in by 31 (20.4%) participants; the mean age of the patients was 13.8, and 19 (61.3%) were ambulant. The video was displayed 127 times. The overall mean rating of the session was 4.77/5, and intelligibility was rated 4.74/5. Fourteen (45.2%) patients declared that they had performed the exercises by themselves or with their caregiver’s assistance; all caregivers declared that it is possible to perform the proposed exercises a few times a week or daily. Only two respondents replied to the invitation for an individual online session. Conclusions: The findings from the study show that respiratory telerehabilitation may be implemented in DMD patients; however, the interest in digital rehabilitation among caregivers of DMD boys in Poland is low. The reason for this situation requires further research.